2015
DOI: 10.1074/jbc.m114.624106
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 2 (CK2)-mediated Phosphorylation of Hsp90β as a Novel Mechanism of Rifampin-induced MDR1 Expression

Abstract: Background: Rifampin is a representative inducer of P-gp, and the only known mechanism is binding between rifampin and PXR. Results: Rifampin directly activates CK2, which phosphorylates Hsp90␤. Consequently, PXR increases, and P-gp expression is induced. Conclusion: A mechanism for inducing P-gp expression by rifampin exposure is newly identified. Significance: A strategy for overcoming P-gp-derived drug resistance is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
(31 reference statements)
2
21
0
1
Order By: Relevance
“…This in turn prolongs the stability and occupancy of the active transcription complex as a whole at the promoter accounting for increased ligand-dependent transcription [98]. This study is corroborated by another report showing that mdr1 (PXR target) gene induction is likely due to increased PXR stability via phosphorylation of its chaperone, heat shock protein (Hsp) 90β [99]. Ligand-induced conformational change of PXR promotes rearrangement of the transcriptional complex into a maximally activated state involving additional p300 recruitment and histone acetylation, thereby accelerating transcription (Fig 7.2).…”
Section: Discussionsupporting
confidence: 53%
“…This in turn prolongs the stability and occupancy of the active transcription complex as a whole at the promoter accounting for increased ligand-dependent transcription [98]. This study is corroborated by another report showing that mdr1 (PXR target) gene induction is likely due to increased PXR stability via phosphorylation of its chaperone, heat shock protein (Hsp) 90β [99]. Ligand-induced conformational change of PXR promotes rearrangement of the transcriptional complex into a maximally activated state involving additional p300 recruitment and histone acetylation, thereby accelerating transcription (Fig 7.2).…”
Section: Discussionsupporting
confidence: 53%
“…In vitro studies using cells derived from intestinal tissues have indicated the pregnane-X receptor as a key player in drug-induced P-gp expression (Maier et al, 2007;Kim et al, 2015). For example, rifampin induces P-gp via casein kinase 2-mediated phosphorylation of heat shock protein 90b, and subsequent stabilization of the pregnane-X receptor (Kim et al, 2015). Thus, increased activation of the pregnane-X receptor might be a good candidate to investigate as a possible mechanism of calorie restriction-induced P-gp expression.…”
Section: Discussionmentioning
confidence: 99%
“…DYRK2 phosphorylates hPXR and facilitates hPXR ubiquitination by UBR5 [104]. In addition to ubiquitination, PXR stabilization was also regulated by the chaperone protein heat-shock protein 90β (Hsp90β) [105]. RIF-activated casein kinase 2 (CK2) was shown to phosphorylate Hsp90β at serine 225 and serine 254.…”
Section: Regulation Of Pxr Through Protein-protein Interaction Andmentioning
confidence: 99%
“…RIF-activated casein kinase 2 (CK2) was shown to phosphorylate Hsp90β at serine 225 and serine 254. The phosphorylation of Hsp90β increased its interaction with PXR and promoted PXR stabilization, consequently increasing the expression of MDR1—an essential mediator of multidrug resistance [105]. …”
Section: Regulation Of Pxr Through Protein-protein Interaction Andmentioning
confidence: 99%